Navigating athlete development in elite sport: Understanding the barriers to the provision of performance lifestyle service in England - Holden, J.; Wagstaff, C. R. D.; Wadey, R.; Brown, P. (Psychology of Sport and Exercise, 2025)
The English Performance Lifestyle (PL) service is a Career Assistance Program that aims to support British elite athletes in their holistic development throughout their time in elite sport to support their mental health and career prospects during and following their careers as athletes. Yet, despite the widespread existence and significant funding dedicated to this service, researchers have identified how it is often not fully embedded or used by sport organizations. Therefore, the aim of this study was to extend previous research by understanding the barriers to the provision of the PL service. Underpinned by ontological relativism and epistemological constructivism, 25 Performance Lifestyle Practitioners (PLPs) working in elite sport participated in a qualitative survey and focus groups. The data were analyzed using reflexive thematic analysis. Four themes were developed: There`s a Mountain to Climb, It`s a Crowded Train, You Need an Elevator Pitch and A Seat at the Performance Table. These themes highlight the barriers PLPs face in supporting athletes with their growth and development during their athletic career. The results offer unique insight into PLPs` roles and the challenges they encounter. As such, we offer practical implications including the importance of organizational support, encouraging athletes to develop a multidimensional identity and a variety of narratives that would offer athletes and practitioners another way to be in elite sport. We also offer recommendations for future research aimed at advancing the practice of PLPs to optimize support for elite athletes, such as including diverse perspectives and including both athlete and practitioner voice in the development of Career Assistance Programs.